(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There have been major shifts in the financial services market in recent years. This transition is not specifically anticipated in relation to large mergers between banks and strategically partnerships between financial parties, but is not likely to be followed by the growing legislative reform of the banking industry and the decline of state involvement of banking relations. Preserving and, in the end, growing market share is the key objective and various approaches have been adopted by all financial entities to retain their clients.